Digestion of feed fractions and intake of heifers fed hydrolyzed sugarcane stored for different periods - Missio, Regis Luis [UNESP]; Oliveira, Mauro Dal Secco de [UNESP]; Sforcini, Mariana Paula Rossi [UNESP]; Rennó, Francisco Palma; Freitas Júnior, José Esler; Elejade, Denise Adelaide Gomes; Ferrari, Viviane Borba [UNESP]; Abud, Guilherme de Carvalho [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
The objective of this study was to evaluate, in Nellore heifers, intake and digestibility of hydrolyzed sugarcane stored for different periods. The experimental design used was a 4 × 4 Latin square, four diets, four Nellore heifers with ruminal cannulas (initial body weight 285.4±23.08 kg and average initial age 14 months) and four periods of 21 days. The diets were composed by fresh sugarcane (time zero) or hydrolyzed sugarcane with addition of 0.5% of hydrated lime, stored for 24, 48 or 72 hours, as the unique forage. Intake and digestibility of feed fractions, nitrogen balance, microbial synthesis efficiency, total number of ruminal protozoans and ammoniacal nitrogen did not significantly change by storing sugarcane with addition of 0.5% of hydrated lime. Sugarcane pH varied quadratically for storage time, with maximum pH of 7.02 after 24 hours from lime addition. Ruminal liquid pH values were higher for heifers fed fresh sugarcane, in comparison with those fed hydrolyzed sugarcane. Sugarcane treated with 0.5% of hydrated lime stored for up to 72 hours does not change ruminal digestion to alter the amount of feed consumed by pubescent Nellore heifers. Thus, lime is a viable technology, once it allows long-duration storage and bee control on treated forage, which contributes to animal feeding logistics.
Keywords: Digestibility; dry matter intake; hydrated lime; microbial protein; Nellore; nitrogen balance